Juhud al-Imam al-Bayhaqi fi ithbat al-'aqidah fi mabhath al-iman bi-al-yawm al-akhir = al-Bayhaqi's efforts in affirming the faith of the last day / Nawaf Mohammed M. AlHarbi - AlHarbi, Nawaf Mohammed M. (2012)
This research contains Imam al-Bayhaqi’s efforts in establishing the belief on issues relating to the life after death or the Last Day to mentionfew such as the signs of the time the torment and blessings of the grave the resurrection the pelvis and intercession the balance of the account the Paradise and the Hell. This study relies on his works on this topic in his efforts on defending ‘the sunni’ the approach of the predecessors who are the Companions of the prophet (peace be upon him) those that follows their footsteps like Imam Ahmad Ibn Hanbal, Malik, Al-Shafi’, Abi Hanifa, Sufyan al-Thauri, and al-‘Awza’i Additionally to serve as response to those that has denied these beliefs. The researcher studies Imam Bayhaqi’s views of belief and evidences to justify these issues and the discussion of some of the themes that violet the methodology and curriculum of the classical Islamic scholars in proving these issues particularly to our topic of discourse regardless of specification or generalization. The researcher follows these literatures and discovered that al-Bayhaqi in justifying these issues and mobilizing evidences had laid down an interesting literatures comprises of good arrangement wonderful and coherent sections and chapters as outlined in some of his books such as the book entitled. The belief and guidance to the way of righteousness’ but detailed in The Resurrection’ and ‘Torment of the Grave and its blessings’ all references directly from the Qur’an the Sunnah and the works of the later scholars. This research serves as eyes opener for those that have interest in knowing about the level capacity and depth of Imam al-Bayhaqi’s knowledge of narration and its significance. The research comes in four chapters which include the biography of al-Bay haqi and his efforts together with Islamic scholars in establishing the belief on issues relating to the life after death or the Last Day. And the al-Bayhqi’s efforts in establishing the belief on issues relating to the torment of the grave and the issues relating to the balance of the account the Paradise and the Hell. Finally researcher concluds that bayhaqi had his effort in unseen world issues basled on the context and occausion an this effont had its impact on many comments.